Relevance of CRISP proteins for epididymal physiology, fertilization, and fertility - Weigel Muñoz, Mariana (2019)
Background: The molecular mechanisms involved in the acquisition of mammalian sperm fertilizing ability are still poorly understood, reflecting the complexity of this process. Objectives: In this review, we describe the role of Cysteine RIch Secretory Proteins (CRISP1–4) in different steps of the sperm journey to the egg as well as their relevance for fertilization and fertility. Materials and Methods: We analyze bibliography reporting the phenotypes of CRISP KO mice models and combine this search with recent findings from our team. Results: Generation of individual KO for CRISP proteins reveals they are key mediators in different stages of the fertilization process. However, in spite of their important functional roles, KO males for each of these proteins remain fertile, supporting the existence of compensatory mechanisms between homologous CRISP family members. The development of mice lacking epididymal CRISP1 and CRISP4 simultaneously (DKO) revealed that mutant males exhibit an impaired fertility due to deficiencies in the sperm ability to fertilize the eggs in vivo, consistent with the proposed roles of the two proteins in fertilization. Interestingly, DKO males show clear defects in both epididymal epithelium differentiation and luminal acidification known to be critical for sperm maturation and storage. Whereas in most of the cases, these epithelium defects seem to specifically affect the sperm fertilizing ability, some animals exhibit a disruption of the characteristic immune tolerance of the organ with clear signs of inflammation and sperm viability defects. Discussion and Conclusion: Altogether, these observations confirm the relevance of CRISP proteins for male fertility and contribute to a better understanding of the fine-tuning mechanisms underlying sperm maturation and immune tolerance within the epididymis. Moreover, considering the existence of a human epididymal protein functionally equivalent to rodent CRISP1 and CRISP4, DKO mice may represent an excellent model for studying human epididymal physiology and pathology.